Epidemiology and Burden of Pediatric Atopic Dermatitis in China - Chien-Chia Chuang; Lydia Braham-Chaouche; Ryan Thomas; Tarek Mnif (Dermatology and Therapy)
Abstract Introduction We aimed to estimate the prevalence, severity, and burden of pediatric atopic dermatitis (AD) in China. Methods EPI-CARE China was a cross-sectional online survey that assessed AD in the general pediatric populations (aged 0.5‒17 years) between 21 March 2021 and 5 April 2021 in China. Diagnosis of AD prevalence was based on both International Study of Asthma and Allergies in Childhood criteria and self-reported or parent-reported physician confirmation of ever having had AD. Severity (mild, moderate, and severe) in the preceding week was assessed by patient global assessment. Health-related quality of life (HRQoL) was assessed using established dermatology patient-reported outcomes tools (Infant Dermatitis Quality of Life and Children’s Dermatology Life Quality Index). Outcomes included type 2 inflammatory comorbidities and itch, skin pain, and sleep disturbance in the previous 24 h (numeric rating scale [NRS]: 0–10 [no symptoms–worst symptoms]), stratified by age group (aged ≤ 5 years, 6–11 years, and 12–17 years). Results In 7148 patients, AD prevalence was 3.2% (≤ 5 years, 3.8%; 6–11 years, 4.1%; 12–17 years, 1.7%). Of these, 59.1% (≤ 5 years, 66.1%; 6–11 years, 60.1%; 12–17 years, 39.4%), 38.8% (≤ 5 years, 33.9%; 6–11 years, 38.0%; 12–17 years, 53.1%), and 2.0% (≤ 5 years, 0.0%; 6–11 years, 1.9%; 12–17 years, 7.5%) had mild, moderate, and severe AD, respectively. Patients with moderate AD reported greater impacts on HRQoL than patients with mild AD (too few patients with severe AD provided HRQoL data for comparison). Overall, 90.5% patients reported ≥ 1 atopic comorbid condition. The mean (SD) itch, skin pain, and sleep disturbance NRS values were 5.9 (2.4), 5.6 (2.6), and 5.9 (2.3), respectively. Conclusions These results demonstrate that AD is associated with substantial patient burden in pediatric patients in China.